Evidence to Action: Research to Address Illegal Wildlife Trade - Milner-Gulland, E. J.; Cugniere, Laure; Hinsley, Amy; Phelps, Jacob; Rolfe, Michael 't Sas; Veríssimo, Diogo (2018)
Tools and expertise to improve the evidence base for national and inte rnational Illegal Wildlife Trade policy already exist but are underuti lised. Tapping into these resources would produce substantive benefits for wildlife conservation and associated sectors, enabling government s to better meet their obligations under the Sustainable Development G oals and international biodiversity conventions. This can be achieved through enhanced funding support for inter-sectoral research collabora tions, engaging researchers in priority setting and programme design, increasing developing country research capacity and engaging researche rs and community voices in policy processes. This briefing, addressed to policy makers and practitioners, is part of the 2018 Evidence to Ac tion: Research to Address Illegal Wildlife Trade event programme, orga nised by five of the UK’s most active IWT research institutions, to su pport the London 2018 IWT Conference.